2011
DOI: 10.1136/oemed-2011-100347
|View full text |Cite
|
Sign up to set email alerts
|

Increased alveolar nitric oxide and systemic inflammation markers in silica-exposed workers

Abstract: In conclusion, measurement of alveolar NO concentration and plasma cytokine and adipokine levels seems to offer a modern means to demonstrate the inflammatory effects of exposure to silica. These measures might be useful in finding subjects with a significant immune response to silica particles and thus at higher risk of developing silicosis or other immunological diseases associated with exposure to silica, but further research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 32 publications
3
45
0
1
Order By: Relevance
“…Recent studies have demonstrated that silicosis is an immune-associated disease as pulmonary silicosis is usually accompanied by abnormalities of immune parameters, and the patients with silicosis have a tendency to suffer from autoimmune diseases (Valletta et al, 1992;Cooper et al, 2002;Carlsten et al, 2007;Sauni et al, 2012). In this study, we found that IgG levels were elevated in patients with silicosis, and that this elevation could be downregulated by MSC therapy.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Recent studies have demonstrated that silicosis is an immune-associated disease as pulmonary silicosis is usually accompanied by abnormalities of immune parameters, and the patients with silicosis have a tendency to suffer from autoimmune diseases (Valletta et al, 1992;Cooper et al, 2002;Carlsten et al, 2007;Sauni et al, 2012). In this study, we found that IgG levels were elevated in patients with silicosis, and that this elevation could be downregulated by MSC therapy.…”
Section: Discussionsupporting
confidence: 53%
“…In this study, we found that IgG levels were elevated in patients with silicosis, and that this elevation could be downregulated by MSC therapy. Increased IgG levels were also reported by Sauni et al, 2012. In a chronic asthmatic mouse model, it was found that administering MSCs could decrease airway inflammation and airway remodeling by elevating IL-12 concentrations and the number of regulatory T cells, resulting in the re-balance of the local immune system (Ge et al, 2013).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our finding is in line with previously published studies that have found increased alveolar NO levels in patients of asbestosis, in asbestos-exposed workers with borderline parenchymal changes in high-resolution computed tomography, and in silica-exposed workers. [11][12][13] The increased alveolar NO levels in dust-exposed participants suggest that dust exposure may induce inflammation in the peripheral parts (alveoli and small airways) of the lungs.…”
Section: Discussionmentioning
confidence: 98%
“…10 Elevated levels of alveolar NO concentration, 8-isoprostane, and LTB 4 in EBC and C-reactive protein (CRP), interleukin-6 (IL-6), interleukin-8 (IL-8), and myeloperoxidase (MPO) in serum have been found after exposure to asbestos or respirable quartz, in addition to patients diagnosed with asbestosis and silicosis, suggesting that occupational exposures may trigger both local and systemic inflammatory responses. [11][12][13][14] The aim of this study was to assess whether dust exposure in foundry work is associated with airway inflammation. Inflammation was assessed by measuring alveolar and bronchial NO output and analyzing levels of inflammatory markers in EBC (8-isoprostane and LTB 4 ) and in serum samples (MPO, E-selectin, IL-6, IL-8, IgE, and CRP).…”
mentioning
confidence: 99%